Interpolação linear logaritmica - Rossi, Rosângela de Lourdes (2015)
This dissertation project aims at the Teaching of Linear Interpolation logarithmic, with the target group students from High school and their teachers to facilitate the meeting of the logarithms of values without the use of board existing common logarithms or the calculating machines. The concepts, the properties of logarithms and interpolations inserted in activities based on the Didactic Engineering are the brand and the engine of development of this work. The materials handling, visualization of results and activities developed by high school students from public schools ensured the originality of the teaching relationship / learning of mathematics, especially in the Linear Interpolation logarithmic, circumscribing on purpose that objective.